Application of taguchi's method on the purifying process of tronoh silica sand via mechanical milling and ultrasonic bath - Hashim, N. (Asian Research Publishing Network, 2016)
The purification of silica sand is usually conducted in order to obtain a required high silica percentage and minimal impurities. However, the impurities in the residue still become the obstruction to obtaining a high purity of silica. An experimental investigation was conducted to explore the purifying process via the ball milling technique, followed by an ultrasonic bath. In this study, the concept of Taguchi's Design of Experiments was applied in order to optimize the processing parameters used to purify Tronoh silica sand. The results reveal that the important parameters influencing the ball milling process were duration of milling, jar volume and ball per powder weight ratio (BPR). At the same time, the results also show the concentration of NaOH, soaking time and ultrasonic temperature were important factors for ultrasonic bath. Therefore, improvements in the purification of the silica sand process were proposed. Â©2006-2016 Asian Research Publishing Network (ARPN).